A Method of Indefinite Krylov Subspace for Eigenvalue Problem. (16th May 2018) - Aliyari, M.; Ghasemi Kamalvand, M.
Abstract : We describe an indefinite state of Arnoldi's method for solving the eigenvalues problems. In the following, we scrutinize the indefinite state of Lanczos' method for solving the eigenvalue problems and we show that this method for the J -Hermitian matrices works much better than Arnoldi's method.